2011
DOI: 10.1007/s11199-011-9960-1
|View full text |Cite
|
Sign up to set email alerts
|

Watching Aggressive, Attractive, Female Protagonists Shapes Gender Roles for Women Among Male and Female Undergraduate Viewers

Abstract: The impact of exposure to media representations of aggressive, attractive, female protagonists on audiences’ gender role expectations for women was explored through a laboratory experiment with 122 undergraduates from a large university on the west coast of the United States. Participants viewed a segment of a major Hollywood motion picture that featured a female protagonist who was either highly attractive or less attractive and either highly aggressive or not aggressive. Viewing clips featuring a female prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
3
8
0
Order By: Relevance
“…This research echoes that of Taylor and Setters (2011) as well as Calvert, Kondla, et al (2001), who found that participants tended to hold stereotypically feminine and stereotypically masculine expectations for women. It seemed that while participants observed the aggressiveness shown in the clip of video, the gender stereotypes they hold also played a major role in how they made meaning from the characters.…”
Section: Chapter 5 Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This research echoes that of Taylor and Setters (2011) as well as Calvert, Kondla, et al (2001), who found that participants tended to hold stereotypically feminine and stereotypically masculine expectations for women. It seemed that while participants observed the aggressiveness shown in the clip of video, the gender stereotypes they hold also played a major role in how they made meaning from the characters.…”
Section: Chapter 5 Discussionsupporting
confidence: 87%
“…For most of these participants, being pretty seemed to serve as an essential condition for being aggressive. Again, the results echo the findings of Taylor & Setters (2011) and Calvert, Kondla, et al (2001) that participants tended to prefer the female characters, if aggressive, to be feminine at the same time.…”
Section: Chapter 5 Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, there has been comparatively little research into the effects of sexual content type on body dissatisfaction or sex schemas. Taylor and Setters [15] found that women watching highly attractive, highly aggressive female film protagonists endorsed both more stereotypically masculine and feminine gender roles for women relative to women watching less attractive and/or less aggressive female protagonists, provided that they also perceived the character as being worthy of emulation. The authors suggest that this is due to spreading activation, whereby the priming of one component of a schema activates the other components.…”
Section: Distinguishing Between Types Of Sexual Contentmentioning
confidence: 99%